Association between homograft tissue exposure and allosensitization prior to heart transplant in patients with congenital heart disease. (10th December 2021) - Donovan, Denis J.; Richmond, Marc E.; Bacha, Emile A.; Addonizio, Linda J.; Zuckerman, Warren A.
Abstract: Background: Surgical repair for patients with congenital heart disease (CHD) often incorporates homograft tissue or other foreign material that can lead to allosensitization. We sought to identify the relationship between pre‐sensitization prior to heart transplant and exposure to homograft tissue in CHD patients. Methods: Retrospective chart review of all CHD patients who underwent heart transplant at a major pediatric transplant center between 1/1/2011‐3/31/18. Operative records determined use of homograft tissue or foreign material. Panel reactive antibody (PRA) and Luminex TM single‐antigen bead (SAB) testing results were reviewed. Statistical analysis determined odds of pre‐sensitization in patients exposed to homograft tissue. Results: Fifty‐six CHD patients underwent transplant during the review period. Thirteen patients (23%) were pre‐sensitized by PRA>10%. By SAB testing, 33 patients (59%) developed any anti‐HLA antibody >0 MFI, 30 patients (54%) >2000 MFI, and 19 patients (34%) >6000 MFI. Patients with homografts were more likely to be pre‐sensitized by PRA (OR = 7.31, p  = .007), and to have developed any anti‐HLA antibody at various levels, >0 (OR = 4.52, p  = .034), >2000 (OR = 8.59, p  = .003), and >6000 (OR = 8.50, p  = .004). Of patients with homografts, those pre‐sensitized by PRA had longer exposure times (9.80 vs 4.96 years, p  = .025). There was no difference in exposure time with relation to pre‐sensitization by SAB testing. Conclusions: Previous exposure to homograft tissue appears to increase the odds of pre‐sensitization by either the PRA or SAB testing. Longer exposure time to homograft tissue prior to transplant is associated with increased pre‐sensitization at transplant as determined by PRA, though not by SAB testing.